Piezogenic pedal papules with mitral valve prolapse - Cihan Altin; Ulku Askin; Esin Gezmis; Haldun Muderrisoglu (Wolters Kluwer Medknow Publications, 2016)
Piezogenic pedal papules (PPP) are herniations of subcutaneous adipose tissue into the dermis. PPP are skin-colored to yellowish papules and nodules on lateral surfaces of feet that typically become apparent when the patient stands flat on his/her feet. Some connective tissue diseases and syndromes have been reported in association with PPP. Mitral valve prolapse (MVP) is a myxomatous degeneration of the mitral valve, characterized by the displacement of an abnormally thickened mitral valve leaflet into the left atrium during systole. MVP may be isolated or part of a heritable connective tissue disorder. PPP, which is generally considered as an isolated lesion, might be also a predictor of some cardiac diseases associated with connective tissue abnormalities such as MVP. A detailed systemic investigation including cardiac examination should be done in patients with PPP. Since in the literature, there are no case reports of association of PPP with MVP, we report these cases.